2005
DOI: 10.1080/10673220500433148
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Uses of Atypical Antipsychotics

Abstract: Atypical antipsychotic drugs are primarily indicated for the treatment of psychotic disorders such as schizophrenia and schizoaffective disorder. Recently, they have also been used for mood stabilization. This article reviews other, potentially therapeutically useful indications for these medications. In most cases, the evidence supporting these new uses is limited but provocative, and involves only case reports. It has not yet been determined whether the usefulness of atypical antipsychotics for nonpsychotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5] It is estimated that 43% to 70% of atypical antipsychotics are used for off-label indications such as insomnia, anxiety, and posttraumatic stress disorder. 6,7 There is limited evidence for the use of atypical antipsychotics in the intensive care unit (ICU) to treat psychiatric symptoms associated with agitation and psychosis, including delirium. [8][9][10][11][12] One of the trials that showed a potential benefit for the use of these agents in the ICU was conducted by Devlin et al in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] It is estimated that 43% to 70% of atypical antipsychotics are used for off-label indications such as insomnia, anxiety, and posttraumatic stress disorder. 6,7 There is limited evidence for the use of atypical antipsychotics in the intensive care unit (ICU) to treat psychiatric symptoms associated with agitation and psychosis, including delirium. [8][9][10][11][12] One of the trials that showed a potential benefit for the use of these agents in the ICU was conducted by Devlin et al in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Some case reports suggest that clozapine, olanzapine, quetiapine and risperidone improve symptoms of obsessive-compulsive disorder (OCD) and panic disorder, while an equal number of reports indicate the worsening effects of each drug on these disorders (Brooke et al, 2005). For other anxiety disorders, such as post-traumatic stress disorder (PTSD), some studies find that atypicals improve certain symptoms (e.g., hyperarousal and reexperiencing) (Hamner, 1996, Monnelly et al, 2003, Petty et al, 2001), while others failed to reach the same conclusion (Butterfield et al, 2001, Hamner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The results have been mixed (Carson et al, 2004). Some case reports suggest that atypicals improve symptoms of obsessive-compulsive disorder and panic disorder, while an equal number of reports indicate the worsening effects on these disorders (Brooke et al, 2005). Preclinical evidence is also inconclusive.…”
Section: Introductionmentioning
confidence: 99%